2022
DOI: 10.3389/fphar.2022.947387
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine monophosphate activated protein kinase contributes to skeletal muscle health through the control of mitochondrial function

Abstract: Skeletal muscle is one of the largest organs in the body and the largest protein repository. Mitochondria are the main energy-producing organelles in cells and play an important role in skeletal muscle health and function. They participate in several biological processes related to skeletal muscle metabolism, growth, and regeneration. Adenosine monophosphate-activated protein kinase (AMPK) is a metabolic sensor and regulator of systemic energy balance. AMPK is involved in the control of energy metabolism by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 214 publications
0
17
0
Order By: Relevance
“…Furthermore, the effect of adenosine on the protein kinases/phosphatase involving muscle adaptation to exercise requires more investigations from animal and cell studies to provide deeper insight into the observed effect related to muscle stem cell homing and expansion. 37…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effect of adenosine on the protein kinases/phosphatase involving muscle adaptation to exercise requires more investigations from animal and cell studies to provide deeper insight into the observed effect related to muscle stem cell homing and expansion. 37…”
Section: Discussionmentioning
confidence: 99%
“…The TGF‐β/Smads signalling pathway is identified as a canonical pathway involved in this regulation 55 . However, it is important to note that other signalling pathways, such as the ERK and mTOR pathways, have also been shown to interact with the AMPKα pathway 23 . Therefore, it is likely that additional pathways contribute to the regulation of mitochondrial dynamics by TGF‐β3 in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…22 AMPK acts as a metabolic sensor, governing mitochondrial dynamics and maintaining energy balance. 23 TGF-β3 is a highly conservative and important growth factor of the TGF superfamily. 8,24,25 TGF-β3 can affect the chondrocyte behaviours to mediate cartilage homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations